Admittance Control of a Multi-Finger Arm Based on Manipulability of Fingers - Takayuki Hori (International Journal of Advanced Robotic Systems, 2011)
In the previous studies, admittance control and impedance control for a finger‐arm robot using the manipulability of the finger were studied and methods of realizing the controls have been proposed. In this study, two 3‐DOF fingers are attached to the end‐effector of a 6‐DOF arm to configure a multi‐finger arm robot. Based on the previous methods, the authors have proposed an admittance control for a multi‐finger arm robot using the manipulability of the fingers in this study. Algorithms of the averaging method and the mini‐max method were introduced to establish a manipulability criterion of the two fingers in order to generate a cooperative movement of the arm. Comparison of the admittance controls combined with the top search method and local optimization method for the multi‐finger arm robot was made and features of the control methods were also discussed. The stiffness control and damping control were experimentally evaluated to demonstrate the effectiveness of the proposed methods.